Analisis Manajemen Pengelolaan Linen Dalam Memenuhi Standar Pelayanan Minimal Di RSUD Tugurejo Provinsi Jawa Tengah - Amalia Alifah; Septo Pawelas Arso; Wulan Kusumastuti (Jurnal Kesehatan Masyarakat, 2019)
Linen is one of the non-medical logistics that plays an important role in providing health services in hospitals. Good linen management will control the incidence of infections in the hospital. Linen is one indicator of minimum service standards in hospitals that must be achieved. Therefore linen must be managed properly. This study aims to analyze the management of linen in meeting the minimum service standards in Tugurejo District Hospital in terms of inputs, processes and outputs. This research is a qualitative research with a descriptive analytic approach. Data collection was carried out by the indepth interview method and selected based on purposive sampling technique. The subject of the research was the Head of Non-Medical Support System, Head of Laundry Installation, 2 Laundry Officers as the main informants. Whereas the triangulation informants were the Head of the Inpatient Room and a nurse.The results showed that in the input aspect there was a shortage of personnel in terms of numbers and had never attended linen management training. The process aspect shows that the implementation of linen management is still not optimal and there are some constraints especially in the linen control section. The output aspect shows that the occurrence of linen is still missing and the inaccuracy in the availability of linen is a result of suboptimal management. This research suggests to increase laundry staff, improve the quality of human resources with certified training, improve linen management processes both linen management in the room and laundry in accordance with SOP, improve coordination between the laundry and head of the room related to recording, reporting and controlling linen by meeting periodically.